2014
DOI: 10.1016/j.ejvs.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Vein Harvesting in Lower Extremity Arterial Bypass: A Systematic Review

Abstract: EVH reduces primary patency rates after LEAB, but does not demonstrate an advantage with respect to postoperative wound complications. However, the available data are heterogeneous, and uncertainty is introduced by both evolution in technology and increasing technical experience. EVH should be used with caution and in the context of formal research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
1
12
0
2
Order By: Relevance
“…24 The cardiac literature has also demonstrated in a randomized controlled trial that endoscopic harvesting is 7 The use of the minimally invasive strategy for vein harvesting was also not associated with improved wound outcomes according to a recent meta-analysis. 26 The findings of this present study are consistent with the results of the meta-analysis as well as our singleinstitution study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…24 The cardiac literature has also demonstrated in a randomized controlled trial that endoscopic harvesting is 7 The use of the minimally invasive strategy for vein harvesting was also not associated with improved wound outcomes according to a recent meta-analysis. 26 The findings of this present study are consistent with the results of the meta-analysis as well as our singleinstitution study.…”
Section: Discussionsupporting
confidence: 92%
“…Although significant heterogeneity was identified among the studies, the selected pooled data demonstrated a significantly higher rate of primary patency loss associated with the endoscopic technique with a hazard ratio of 1.29. 26 In studies in which the primary patency beyond 1 year is reported, several have demonstrated a significantly higher rate of delayed patency loss for the grafts harvested endoscopically. [13][14][15][16] In two of three studies that we identified reporting comparable delayed primary patency rates for open and endoscopic harvest techniques, 5,7,12 all the endoscopic harvesting procedures were performed by a single surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to reduce the rates of wound complications and infection associated with vein harvesting, endovascular harvesting (EVH) techniques have been developed; however, recent evidence suggests this approach confers no difference in wound complications, infection, or patency. 33,34 One recent systematic review demonstrated that EVH may actually significantly reduce primary patency rate and confer no benefit in terms of wound healing, 35 and this technique is therefore not recommended by the authors.…”
Section: The Conduitmentioning
confidence: 99%
“…Typically, OVH comprises of either one long incision or 'bridged' incisions across the vein (2). Accordingly, this technique is characterized by discomfort and risks of complications such as edema, hematoma, postoperative pain, wound dehiscence and infection, delayed healing, cellulitis, and loss of mobility, which lead to greater costs due to the prolonged hospital stay or readmissions (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…As a procedure developed to eliminate the necessity for long incisions accompanied by open harvesting, EVH decreases the related complications compared to OVH and also contributes to higher patient satisfaction and the improved life quality of the patients. Moreover, it stands as the preferred technique for conduit harvest in numerous cardiothoracic centers (2,3,5). However, several concerns still remain regarding the impact of endoscopic harvesting on the mid-and long-term outcomes (2, 3, 6, 7).…”
Section: Introductionmentioning
confidence: 99%